Edmodo as An Online Instructional Delivery Technique for Sustaining Teaching and Learning Activities in Covid-19 Era in Public Universities in North-Central, Nigeria - Martin Afen Olofu; Paul Agbade Olofu (MO.RI Publishing, 2021)
This study centered on Edmodo as an online instructional delivery technique for sustaining teaching and learning activities in covid-19 era in public universities in North-Central, Nigeria. The study was guided by two objectives and two research questions and one hypothesis. This study adopted descriptive survey and quasi-experimental research designs. The sample of the study comprised 100 students in two universities (each for treatment and control groups) and 7008 lecturers drawn from three public universities in North-Central, Nigeria. Stratified and simple random sampling techniques were used for selecting universities and the sample of the study. First, stratified sampling was used to group both lecturers and students into two strata. Thereafter, simple random sampling was used to select the universities and sample of the study; using lottery method with replacement. 10% proportionate sample was used to select the lecturers. Curriculum Studies Achievement Test (C-SAT) and questionnaire were used as instruments for data gathering. Data collected were analyzed with simple percentage, mean and t-test statistical techniques. Finding showed that the level of awareness of university lecturers on Edmodo as a technological instructional delivery technique is very low or poor. It was also indicated that there is significant difference between the mean achievement scores of university students taught curriculum studies with Edmodo and their counterparts taught with lecture technique; as those in the treatment group performed better than those in control group. The study recommended that: school management, the government and ICT-related Non-governmental organizations should help in organizing workshops and seminars for lecturers in order to advance their knowledge and awareness on ICT usage especially Edmodo and others. Also, since the students who were taught with Edmodo significantly performed better than their counterparts in the control group who were taught with lecture method, lecturers should be encouraged to use Edmodo for teaching and learning.